Relationship of autistic traits and the severity of fear of the COVID-19 pandemic in the general population - Bieczek, Dominika; Ściślicka, Adrianna; Bobowska, Agnieszka; Tomsia, Filip; Wilczyński, Krzysztof Maria; Janas-Kozik, Małgorzata (Frontiers in Psychiatry, 2024)
Background The aim of the study was to investigate the level of fear of the COVID-19 pandemic and to detect a possible correlation between the autistic traits and the level of fear and to learn about other factors that may affect the level of fear. Methods The study utilised a questionnaire and was conducted online in the period from 16.02.2021 to 11.06.2021. The test group consisted of 214 respondents with an average age of 23.78 years (95%CI: 22.48 – 25.08; max: 61, min: 14) from the general population. The study used The Autism-Spectrum Quotient (AQ) questionnaire to assess the degree of autistic traits in the general population and The Fear of COVID-19 Scale, which was used to assess the level of fear of COVID-19. Results Among the respondents, 9 people scored ≥32 on the AQ test and were considered to have a high degree of autistic traits. In multiple regression (R2 = 0.1, p<0.0001), a positive relationship between the severity of fear of COVID-19 and the autistic traits (p=0.01) and age (p<0.001) was obtained. Additionally, a second multiple regression (R2 = 0.1, p<0.000001) including the subscales of AQ was performed and a positive relationship between the severity of fear of COVID-19 and the difficulties in attention switching (p=0.0004) and age (p=0.00001) was obtained. Conclusion People with higher autistic traits present greater fear of the COVID-19 pandemic. We suggest that it might be caused by cognitive stiffness and disorders in emotions regulation, according to the literature. The elderly also present higher levels of fear. The other variables did not affect the level of fear of the COVID-19 pandemic.